Korn og arkitektur.: Overgangen mellem sten- og bronzealderen ved Revsinggård II - Mehlsen, Simone Nørgaard; Christensen, Silja Arnfridardottir (Arkæologi i Slesvig-Archäologie in Schleswig, 2023)
During the spring and summer of 2020, traces of a settlement dating to the Neolithic Period and Bronze Age were archaeologically excavated just north of present-day Vejen in the central part of Southern Jutland. The site was inhabited at a time of major societal changes at the end of the Neolithic Period. During the excavation traces from several houses were found, dating primarily between the Late Neolithic and the Late Bronze Age, with the majority of the houses around 2000 BC. The site contained both two- and three-aisled longhouses as well as a so-called »hybrid house«, which combines these two types of construction. It is far from the first time a hybrid house has been excavated in Jutland, but only few have so far been published. These houses can contribute to new information regarding the introduction of three-aisled houses in Southern Scandinavia. Furthermore, several pits containing large amounts of charred grains were excavated. An archaeobotanical analysis of these grains has provided information about what the inhabitants chose to cultivate and consume, as well as information about how crops etc. were stored. The results showed that the main crop at Revsinggård II was naked barley with a supplement of emmer/spelt wheat. These analyses have also given information about the activities within the wider area surrounding the houses and demonstrated how important a good sampling strategy is for further archeological research.